(untitled) (Revista Innova Educación, 2021)
Schools in Perú have not typically been the sites of research on meditation or its possible role in student health or primary and secondary education outcomes. This retrospective observational study seeks to begin redressing this evidentiary shortfall by confirming results from an earlier, smaller-scale study of 91 students in Huay-Huay, with a specific focus on the practice of Transcendental Meditation at Peruvian schools, some in remote locations with indigenous students. Five hundred and twenty primary and secondary students at four schools in Lima, Cusco, Puno, and Ventanilla were asked to rate their experience of meditation and its relation to four factors using a paper-and-pencil questionnaire: physical health; cognitive health; emotional health; and school performance. An average of 66% of students agreed they had benefited from practice of Transcendental Meditation in each area of health and school performance, and regularity of practice was a moderate predicator of higher scores on each variable. These quantitative findings are suggestive of a role to be played by the addition of Transcendental Meditation to primary and secondary school curricula in Perú.